Genotype‐phenotype correlation and risk stratification in a cohort of 123 hereditary stomatocytosis patients - Andolfo, Immacolata; Russo, Roberta; Rosato, Barbara Eleni; Manna, Francesco; Gambale, Antonella; Brugnara, Carlo; Iolascon, Achille (American journal of hematology, 2018)
Hereditary stomatocytoses (HSts) are a wide spectrum of hemolytic anemias in which the erythrocyte membrane cation permeability is increased. Dehydrated hereditary stomatocytosis is the most frequent among HSts. It is caused by missense mutations in PIEZO1 and KCNN4 genes. We described 123 patients enrolled in our Genetic Unit from 2013 to 2017. Overall HSt subjects exhibit macrocytic mild anemia. We found that PIEZO1 is the most frequent mutated gene within our families (47% of pedigrees). In 59.1% of cases the mutations localized in the nonpore protein domain, while in 40.9% of patients they localized in the central pore region. The genotype‐phenotype correlation analysis on 29 PIEZO1‐patients demonstrated that most of severely affected patients carried mutations in the pore domain, suggesting that the severity of this condition is related to the pore properties and intracellular domain that could be responsible of interactions with intracellular components. This is the first cohort study on a large set of hereditary stomatocytosis patients, stratified according to their causative gene useful for diagnosis, prognosis, and management of these patients.